GLOBAL PERSPECTIVES A Handbook for Understanding Global Issues - Kelleher, Ann; Klein, Laura (Prentice Hall, 1999)
This book provides a multidisciplinary vocabulary for explaining general issues or trends facing the contemporary world involving cultural diversity, economic development, the natural environment, and international peace and violence. It affords equal time to the analysis of global issues using alternative perspectives. Four major case studies?one for each of the four central issues explored?encourage the application of concepts and perspectives presented in the narrative.